Avaliação da sustentabilidade de tecnologias de captura de CO2 através da MCDA - Barreto, Arthur Esteves da Costa Mothé (2023)
It is known that the concentration of CO2 in the atmosphere recorded values of 280 ppm before the Industrial Revolution (1860), which today is around 400 ppm and that as a consequence of this, global warming and climate change are happening quickly then ever. To contain this imbalance, Carbon Capture and Storage (CCS) and Carbon Capture Utilization for Sequestration (CCUS) have been fundamental technologies, however, like any process, they can generate different impacts. Thus, the objective of this work is to evaluate the sustainability of carbon capture technologies using the MCDA methodology and sustainability indicators, as an aid to decision making, as well as the proposition of improvements to the SiCSeGE technology developed by the startup DeCARB. Comparative technologies of interest were defined as those already established in the international market, belonging to Carbon Clean and Carbon Engineering. The methodology used for the sustainability assessment was developed from the adaptation of an MCDA approach, using Excel and RISK Simulator software, which allows the simultaneous assessment of environmental, social, economic and engineering criteria. Thus, after methodological validation and using official information from the companies involved about the established indicators and metrics, the "DeCARB" technology resulted in a higher sustainability index, specifically with a better average in the GWP criteria, public perception, cost of capture and storage potential. On the other hand, the lowest performance criteria of the DeCARB project provided a reflection on possible improvements for the competitive growth of this startup.